Analysis of the Influence of Flight Altitude on the Accuracy of Elevation Derived from UAV-Photogrammetry - Helik Susilo; Dandung Novianto; Trias Rahardianto; Muhamad Fajar Subkhan; Martince N Bani; Muhammad Tri Aditya (Westscience Press, 2026)
Accurate elevation measurement is critical for applications such as construction engineering, land subsidence monitoring, and infrastructure management. Conventional terrestrial surveying using a Total Station provides reliable results but is labor intensive and time consuming. UAV-Photogrammetry offers a more efficient alternative by enabling rapid elevation estimation from aerial imagery acquired by camera equipped unmanned platforms. In this study, aerial photos were collected at three flight altitudes, 25 m, 35 m, and 45 m above ground level (AGL), and elevations derived from UAV-Photogrammetry processing were compared against Total Station measurements. The results demonstrate that imagery captured at 25 m AGL achieved the highest accuracy, with a Root Mean Square Error (RMSE) of 0.0313 m, followed by the 35 m AGL (RMSE = 0.0539 m) and 45 m AGL (RMSE = 0.1118 m). Statistical evaluation using a t-test indicated no significant differences between UAV-Photogrammetry elevations and those obtained from the Total Station.